Regulation of interpersonal distance in virtual reality: Implications for socio-emotional functioning in late adulthood - Bozana Meinhardt-Injac; Isabelle Boutet; Laurence Chaby; Christoph von Castell; Robin Welsch (PLoS ONE, 2025)
Objective Accurately interpreting emotional states from facial expressions is crucial for effective social interactions. This study investigates age-related differences in interpersonal distance (IPD) regulation and emotion recognition using a virtual reality (VR) environment. We examined how younger and older adults adjust their IPD in response to emotional expressions from virtual agents. Methods Eighty participants, divided into older adults (OA) and younger adults (YA), took part in the study. Participants were immersed in a VR setup where they engaged in social interactions with happy or angry looking virtual agents. This behavioral task was complemented by a standardized emotion recognition task (ERT). Results Results showed that both YA and OA preferred larger distances from angry-looking virtual agents compared to happy ones. No significant differences in IPD were found between the age groups. However, older adults were less accurate in recognizing facial expressions. Conclusion These findings suggest that older adults can effectively regulate their social distance despite potential challenges in emotion recognition. The study underscores the importance of considering cognitive, perceptual, and motivational factors when examining the dynamics of emotional recognition and interpersonal distance in social contexts.